Effect Of Open-Pit Blasting Vibrations on a Hanging-Wall Slope: A Case Study of the Beizhan Iron Mine in China - Yong-gang Xiao; Jie Cao; Xiao-min Liu; Chang-hong Li (Geofluids)
With the increase in the depth of large-scale open-pit mining, many mines have to face problems such as what is the effect of open-pit blasting on the rock slope and how to ensure the stability of a high-steep slope. The east slope of the Beizhan iron mine in Hejing County, Xinjiang, belongs to the typical open-pit high and steep slope of mined hanging-wall ore. To study the effect of open-pit blasting vibrations on hanging-wall slope stability, the intelligent blasting vibration detector was used to monitor the open-pit blasting wave of the Beizhan iron mine and the corresponding numerical model was established. We fitted the transmission law of slope blasting vibration by Sodev’s regression formula and calculated stress, strain, and vibration velocity of the whole slope by numerical simulation. The result showed that the fitting functional relationship was correct and could be the basic rule of predicting the maximum charge amount per delay interval and minimum safe distance for this area. The estimated open-pit blasting charge weight was reasonable and blasting vibrations would have little effect on the hanging-wall slope. The research method and conclusions in this article have numerous reference values for studying the hanging-wall slope’s kinetic stability.